Congenital melanocytic nevi – a literature review - Staniszewska, Izabela; Baran, Milena; Kazimierska, Karolina (Quality in Sport, 2024)
Introduction: Congenital melanocytic nevi (CMN) are small, congenital pigmented moles on the skin that may appear after or shortly after the birth of a child (up to 12–24 months of age). CMN usually increases proportionately with the baby's physical development and occupies the same area of skin as at birth. The incidence of CMN among newborns is relatively low and ranges from 0.2% to 6%. Purpose of work: To collect information on the congenital melanocytic nevi. Summary: The initial step in caring for a patient with CMN involves obtaining a history and conducting a physical examination. We are able to examine the CMN using dermatoscopy, confocal microscopy, and histopathological examination. Melanoma is not common in people with CMN, but it can develop, so it is worth maintaining oncological vigilance and checking them regularly. In our literature review, we reviewed the clinical presentation of CMN and the dermatoscopic image, as well as the light microscopic and confocal microscopic picture of congenital melanocytic nevi.